Digital Bootstraps: Teacher Discourse on Online Learning with Elementary Students - Mueller, Amy (Social Education Research, 2025)
The discourses educators engage with and through shape how they position themselves and their students, constructing powerful storylines through their speech acts. This article examines how educators frame equity in online learning, revealing a dominant cultural narrative: educators perceive themselves as burdened by the growing demands of social inequity, yet powerless within a static and unsupportive system. This often leads to the adoption of a neoliberal "bootstrap" ideology, where students and families are expected to overcome systemic barriers through individual effort—an approach that ultimately reinforces existing inequities. These narratives also expose a deeper crisis in education: the disempowerment and deprofessionalization of educators themselves.